Monitoring and evaluation in program and project management in Zimbabwe: a case study of the women’s development fund in Harare metropolitan province 2010-2014 - Muvuni, Tinotenda H. (Midlands State University, 2018)
States are required to conform to stringent project and program reporting requirements in order to satisfy the wide range of stakeholders. Project and program monitoring and evaluation (M&E) systems, frequently a requirement for funding, are believed to inform the reporting process. The role of the state has evolved over the past years and it is readily apparent that good governance has progressively become key in the attainment of sustainable socioeconomic development. The demands of the global economy, new technology and new information is continuously challenging the state and it calls for greater democracy and participation. According to the national monitoring and evaluation policy (2015) a robust monitoring and evaluation system in Government is highly significant for successful implementation of national development policies, programmes and projects and to ensure efficient and effective service delivery. This research sought to present monitoring and evaluation in its various forms and dimensions. It highlighted its importance, contributions and efficacy in program and project management and implementation, focusing on the Women’s Development Fund (WDF) in Harare metropolitan province 2010-2014.